New era of dialysis: expanded haemodialysis (HDx) - Ivanov, D.D. (KIDNEYS, 2021)
The article is addressed to practical physicians involved in renal replacement therapy, mainly haemodialysis (HD). The article presents a new method for haemodialysis — expanded haemodialysis, assesses its efficiency, and is focused on the problem of large medium molecules elimination. The essence of the method is to use the THERANOVA haemodialyser with the usual infrastructure. The term expanded HD (HDx) has been proposed to determine a method where diffusion and convection are conveniently combined in THERANOVA dialysis with a hollow fibre and equipped with a membrane for middle cut-off. A standard dialysis device can easily perform this technique without special software or additional sophisticated technology. To achieve optimal clearance in the system blood flow 300 ml/min and dialysate flow ≥ 500 ml/min is sufficient. In HDx, the convection flow is supported by internal filtering, but it is offset by the reverse filtering mechanism inside the filter. The special configuration of the membrane with reduced inner diameter provides high convection rates thanks to the combined pre- and post-dilution configuration. Thus, the use of THERANOVA gives to the haemodialysis capabilities of haemodiafiltration. However, the THERANOVA dialyser should not be used for haemodiafiltration in a reason of a potential enlarging of albumin removal. Expanded haemodialysis is advisable to be used in patients with complications associated with the effects of uremic toxins. Expanded haemodialysis may be a rational therapy for patients who are moving from peritoneal dialysis to HD while waiting for transplantation, which is an example of an individualized, personified approach.